2017
DOI: 10.4067/s0718-95162017005000002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic and inorganic manures on maize and their residual impact on soil physico-chemical properties

Abstract: Organic and inorganic nutrients are important for crop productivity and soil health. Present study investigated the effects of organic and inorganic manures on maize and their residual impacts on soil physico-chemical characteristics. Sheep manure (SM), poultry manure (PM) and farmyard manure (FYM) were applied as organic nutrient source while urea, diammonium phosphate (DAP) and sulphate of potash (SOP) were used at different concentrations as inorganic nutrients source viz., T 1 : Unfertilized control; T 2 :… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
128
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(164 citation statements)
references
References 19 publications
28
128
0
8
Order By: Relevance
“…This implied that the integrated use of organic and mineral fertilizers resulted in yield benefits greater than using them alone. Similar results were also reported on barley (Agegnehu et al 2016a;Assefa 2015), wheat (Demelash et al 2014;Getachew et al 2014b), teff (Getachew et al 2014b), maize (Mahmood et al 2017;Wakene et al 2005), Okra (Afe and Oluleye 2017) and tomato (Rajaie and Tavakoly 2016). The improved yields of malting barley due to combined application of organic and mineral amendments resulted from positive changes to the soil, including increased soil pH, available P and total N, and possibly other macro-and micronutrients.…”
Section: Yield and Yield Components Of Malting Barleysupporting
confidence: 74%
“…This implied that the integrated use of organic and mineral fertilizers resulted in yield benefits greater than using them alone. Similar results were also reported on barley (Agegnehu et al 2016a;Assefa 2015), wheat (Demelash et al 2014;Getachew et al 2014b), teff (Getachew et al 2014b), maize (Mahmood et al 2017;Wakene et al 2005), Okra (Afe and Oluleye 2017) and tomato (Rajaie and Tavakoly 2016). The improved yields of malting barley due to combined application of organic and mineral amendments resulted from positive changes to the soil, including increased soil pH, available P and total N, and possibly other macro-and micronutrients.…”
Section: Yield and Yield Components Of Malting Barleysupporting
confidence: 74%
“…Bulluck et al, (2002) reported higher level of P in soil with application of organic manures compared to synthetic soil fertility amendments and also found that K concentration in soils amended with organic amendments increased by a factor of three as compared to soils with synthetic fertility amendments, whereas the K concentrations decreased over time in soils with synthetic fertilizers. Mahmood et al, (2017) studied the effects of organic and inorganic manures on maize and their residual impact on soil physico-chemical properties Results showed that growth and yield of maize were substantially improved by fertilizer application alongside organic manures whereas soil total organic C and total N, P, K contents increased when inorganic fertilizers were applied alone or in combined with organic manures. However, soil pH and soil bulk density decreased due to application of organic fertilizer and showed a negative correlation with grain yield.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…The use of organic soil amendments has been associated with desirable soil properties including increased water holding capacity, cation exchange capacity and lower bulk density and can foster beneficial microorganisms (Bulluck et al, 2002). Organic amendments also improve soil chemical properties such as supply and retention of soil nutrients and can promote favourable enzyme reactions (Mahmood et al, 2017). Management systems that rely on organic inputs as plant nutrients have different dynamics of nutrient availability from that involving the use of chemical fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of compost had positive effects on the soil nutritional status, microbial community structure, and enzyme activity in different stages of barley cultivation (Moreno et al, 2017). Application of organic manures had significant influence on organic carbon depleted arable soils by improving maize productivity and soil physico-chemical properties (Mahmood et al, 2017). Also, residue addition frequency strongly influenced soil respiration, microbial biomass and nutrient availability after addition of low C/N residue, for example, young faba bean (Vicia faba L.) (Zheng and Marschner, 2017).…”
Section: Discussionmentioning
confidence: 99%